A universal mobility-based indicator for regional health level. (January 2022) - Zhang, Haoran; Chen, Jinyu; Chen, Qi; Xia, Tianqi; Wang, Xin; Li, Wenjing; Song, Xuan; Shibasaki, Ryosuke
Abstract: Human mobility is attracting more attention in public health research; however, the existing paradigms typically lack a universal indicator to reveal the underlying mechanism for both urban and rural cases. Based on the large-scale datasets, including national survey, census, and billions of GPS trajectories, we found that the preference for choosing vehicles for travel can be a powerful and universal indicator for regional health levels. Firstly, we showed reliable evidence on the correlation among travel environment, travel behaviors, and health level. Then, we proposed a new travel inverse preference index that is a reliable measurement of unhealthy lifestyle levels and the age-corrected mortality rates within a particular region. The result further showed that multiple spatial environment factors, such as urbanization level, climates, and local walkability, are also strongly related to the indicator. Additionally, we conducted a comprehensive spatial analysis to develop strategic policies that the government could adopt for potential social improvement. Highlights: Based on billions of GPS trajectories, we found vehicle travel preference is a universal indicator for regional health level. The relationship between travel preference and unhealthy lifestyle level is the key to connect human mobility and health. Travel inverse preference index is proven to be a better indicator to represent the social trend of travel mode preference.